Optical scattering from graphene foam for oil imaging/sensing. Issue 76 (28th July 2016) - Deng, Sunan; Kidambi, Piran R.; Butt, Haider; Sabouri, Aydin; Sohail, Manzar; Khan, Safyan A.; Jiang, Kyle
Abstract : This work studied a new way of sensing oil leaks using graphene foam through an optical imaging and light scattering method. Abstract : Oil spill detection is crucial, from an environmental perspective and in view of the associated economic losses. Current optical oil sensing techniques, such as underwater microscopy and light scattering methods, mainly focus on detecting the properties of particles or organisms in water and often require costly equipment and sophisticated data processing. Recent studies on graphitic foam show its extraordinary pollutant absorbing properties, with high absorption weight ratios. Here we propose to produce a graphene foam based ultra-light material that changes its optical properties on absorbing oil species. The results demonstrate clear changes in optical transmission and scattering properties of graphene foam when exposed to various oils. The effective graphene foam sorbent can be easily integrated with optical fiber systems to detect the optical property variations and also to monitor oil presence/spillages remotely. Such sensors can also be used for underground oil exploration.